An Analysis of Physical Activity, Self-Confidence, and Gross Motor Skills of Students in the High and Low Lands of Central Java - Wahyuningtyas Widagti; Hadi (Journal of Physical Education and Sports, 2026)
This study aimed to analyze the relationships between physical activity and self-confidence with gross motor skills among elementary school students living in highland and lowland areas of Central Java, Indonesia. A descriptive quantitative design with a cross-sectional approach was employed. The participants were 80 students in Grades 4–6 (40 from highland schools and 40 from lowland schools). Physical activity was measured using the Physical Activity Questionnaire for Children (PAQ-C), self-confidence using a scale adapted from Lauster, and gross motor skills using the Test of Gross Motor Development-2 (TGMD-2). Data met the assumptions of normality, linearity, and homoscedasticity. Pearson correlation and multiple linear regression analyses were conducted separately for highland and lowland groups. The results showed that physical activity correlated positively and significantly with gross motor skills in both highland (r = 0.488, p = 0.001) and lowland (r = 0.518, p = 0.001) groups. Self-confidence also demonstrated a positive and significant correlation with gross motor skills in both regions (r = 0.410 and r = 0.408, p = 0.009). Regression analyses indicated that physical activity and self-confidence together explained 32.9% of the variance in gross motor skills in the highland group and 36.3% in the lowland group, with physical activity emerging as the stronger predictor. These findings suggest that both behavioural and psychological factors jointly support children’s gross motor development, and that physical education programs should simultaneously promote active lifestyles and self-confidence, tailored to the specific characteristics of highland and lowland environments.